2007
DOI: 10.1021/jp074455n
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Structures of Phthalocyaninatozinc and Hexadecafluorophthalocyaninatozinc Studied by Gas-Phase Electron Diffraction and Quantum Chemical Calculations

Abstract: The molecular structures of phthalocyaninatozinc (HPc-Zn) and hexadecafluorophthalocyaninatozinc (FPc- Zn) are determined using the gas electron diffraction (GED) method and high-level density functional theory (DFT) quantum chemical calculations. Calculations at the B3LYP/6-311++G** level indicate that the equilibrium structures of HPc-Zn and FPc-Zn have D4h symmetry and yield structural parameters in good agreement with those obtained by GED at 480 and 523 degrees C respectively. The calculated force fields … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
30
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 52 publications
4
30
0
Order By: Relevance
“…It is worth mentioning that the recent X-ray studies [26] on three axial ZnPc•••n-alkylamines nicely agree with our data and prove the existence of similar nonplanar structures with d parameter of about 0.5 Å. In addition, the subsequent B3LYP/6-31+G(d) [70] b HF, B3LYP, and MP2 with 6-31G* result from [41] c UB3LYP/6-31G(d,p) data for ZnPc, from [71] d B3LYP/6-31G** data from [34] e B3LYP/6-31G* data for ZnPc, from [72] f X-ray data for ZnPc, from [20] g ED data from [21] h Reinvestigation of ED data from [22] i ED data for SnPc, from [22] j ED data for MgPc, from [22] k Laser-desorption supersonic jet spectroscopy data for H2Pc with D 2h symmetry; planar are also MgPc and ZnPc with D 4h symmetry, from [27] l ED data from [35] [75] e X-ray data for ZnPc•••n-hexylamine, from [24] calculations by these authors [26] closely reproduced the observed crystal structure of these solvates (d was about 0.43 Å …”
Section: Structural Feature Of the Znpc···h 2 O Complexmentioning
confidence: 99%
See 1 more Smart Citation
“…It is worth mentioning that the recent X-ray studies [26] on three axial ZnPc•••n-alkylamines nicely agree with our data and prove the existence of similar nonplanar structures with d parameter of about 0.5 Å. In addition, the subsequent B3LYP/6-31+G(d) [70] b HF, B3LYP, and MP2 with 6-31G* result from [41] c UB3LYP/6-31G(d,p) data for ZnPc, from [71] d B3LYP/6-31G** data from [34] e B3LYP/6-31G* data for ZnPc, from [72] f X-ray data for ZnPc, from [20] g ED data from [21] h Reinvestigation of ED data from [22] i ED data for SnPc, from [22] j ED data for MgPc, from [22] k Laser-desorption supersonic jet spectroscopy data for H2Pc with D 2h symmetry; planar are also MgPc and ZnPc with D 4h symmetry, from [27] l ED data from [35] [75] e X-ray data for ZnPc•••n-hexylamine, from [24] calculations by these authors [26] closely reproduced the observed crystal structure of these solvates (d was about 0.43 Å …”
Section: Structural Feature Of the Znpc···h 2 O Complexmentioning
confidence: 99%
“…In 1999, Fink and co-workers [22] reported on both gas-phase electron diffraction and theoretical DFT studies on the planar equilibrium structure of ZnPc while the BLYP/6-31G* and BLYP/6-31G** data produced a nonplanar molecule with zinc ion about 0.075 Å above the ligand plane [34]. Another experimental electron diffraction and DFT study proposed a planar structure of ZnPc [35]. These authors also obtained a planar D 4h structure using B3LYP density functional and large basis sets of 6-311++G** and cc-pVTZ quality.…”
Section: Introductionmentioning
confidence: 99%
“…Despite intensive investigations of these compounds by different methods, at present the molecular structures of only five nonsubstituted metal phthalocyanine MPc, where M = Sn, Mg, Zn, Cu, and Ni, were studied by gas-phase electron diffraction (GED) method [5][6][7]. The first gasphase structure of CuPc complexes determined by gas electron diffraction was published more than 10 years ago [5].…”
Section: Introductionmentioning
confidence: 99%
“…In the studies of the aforementioned compounds, the authors [5][6][7] paid special attention to the determination of the position of the metal ion relative to N 8 C 8 plane of ring. For complex SnPc [5] the displacement of the metal ion out of the plane of the phthalocyanine fragment was found to be 1.0(1) Å .…”
Section: Introductionmentioning
confidence: 99%
“…Such level of theory has been found to yield accurate structural parameters in earlier combined (experimental and theoretical) studies of oxotitanium phthalocyanine [2] and other large macroheterocyclic molecules. [16][17][18][19][20] Singlet and triplet excited states and the electronic spectra were studied using time-dependent density functional theory (TDDFT) implemented in PC GAMESS 7.0. [9] In all four molecules the molecular orbitals formed mostly by 1s orbitals of C, N, and O atoms, namely 25 first (lowest energy) orbitals in oxozirconium porphyrin and porphyrazine, 33 in octamethylporphyrin and 41 in phthalocyanine, were excluded ("frozen") from the TDDFT calculations.…”
Section: Computationalmentioning
confidence: 99%